THE EFFECT OF STORAGE TIME AND HENS AGE ON ALBUMEN INDEX AND YOLK INDEX OF CHICKEN EGGS - A,, PUTRI; GARNIDA, D.; INDRIJANI, H. (Majalah Ilmiah Peternakan; Vol 26 No 3 (2023): Vol. 26 No. 3 (2023)DO - 10.24843/MIP.2023.v26.i03.p09, 2024)
Eggs are a source of animal protein with affordable price and become popular among consumers. But, the quality of eggs would be rapidly decreased when the eggs are stored for long time. Egg quality can be influenced by many factors, such as temperature and humidity, hens age, and storage time. This study aims to determine the effect of storage time and hens age on the albumen index and yolk index of chicken eggs. This study used an experimental method with a Completely Randomized Nested Design with storage time of 5, 10, 15 and 20 days nested for 38 and 70 weeks of hens age. The results showed that hens age did not have a significant effect (P>0,05) on the albumen index and yolk index, while storage time nested on hens age had a significant effect (P<0,05) on the albumen index and yolk index. The results showed that eggs from 38 weeks old hens were still suitable for consumption after 15 days of storage time with albumen index and yolk index values of 0,0397 and 0,3032. At the age of 70 weeks, eggs can be consumed for a maximum of 10 days of storage time with albumen index and yolk index values of 0,0507 and 0,3541.